Strong evidence for genotype–phenotype correlations in Phelan-McDermid syndrome: results from the developmental synaptopathies consortium. Issue 4 (24th September 2021) - Levy, Tess; Foss-Feig, Jennifer H; Betancur, Catalina; Siper, Paige M; Trelles-Thorne, Maria del Pilar; Halpern, Danielle; Frank, Yitzchak; Lozano, Reymundo; Layton, Christina; Britvan, Bari; Bernstein, Jonathan A; Buxbaum, Joseph D; et al.
Abstract: Individuals with Phelan-McDermid syndrome (PMS) present with a wide range of developmental, medical, cognitive and behavioral abnormalities. Previous literature has begun to elucidate genotype–phenotype associations that may contribute to the wide spectrum of features. Here, we report results of genotype–phenotype associations in a cohort of 170 individuals with PMS. Genotypes were defined as Class I deletions (including SHANK3 only or SHANK3 with ARSA and/or ACR and RABL2B ), Class II deletions (all other deletions) or sequence variants. Phenotype data were derived prospectively from direct evaluation, caregiver interview and questionnaires, and medical history. Analyses revealed individuals with Class I deletions or sequence variants had fewer delayed developmental milestones and higher cognitive ability compared to those with Class II deletions but had more skill regressions. Individuals with Class II deletions were more likely to have a variety of medical features, including renal abnormalities, spine abnormalities, and ataxic gait. Those with Class I deletions or sequence variants were more likely to have psychiatric diagnoses including bipolar disorder, depression, and schizophrenia. Autism spectrum disorder diagnoses did not differ between groups. This study represents the largest and most rigorous genotype–phenotype analysis in PMS to date and provides important information for considering clinical functioning, trajectories and comorbidities as a function of specific genetic alteration.